(untitled) (Communication & Society, 2017)
Active and effective citizen political participation is one of the main manifestations of the existence of a healthy and well consolidated democracy. It has been found that media consumption is a significant predictor for the development of this civic participation. The Communication Mediation Model (O-S-R-O-R) set out an indirect effect that exposure to media messages have on citizen participation, by means of the development of orientations subsequent to consumption and reasoning of the message. Political sophistication is among these orientations promoted by the media, understood as the general level of knowledge on the political system (factual) or the (electoral) campaign acquired by the citizens under media exposure. With the objective of determining its mediating effect on the increase of citizen participation, an analytical survey was conducted in the state of Nuevo León, Mexico, right after the 2015 gubernatorial elections. Findings reflect a mediating role played by factual political sophistication in explaining offline political and civic participation. However, electoral political sophistication worked better to achieve an indirect effect on online political participation.